Analysis of Anomalous Dynamic Responses of Fiber Metal Laminates Under Pulse Loading - Zhai, Hongbo; Zhu, Jianwei; Mao, Boyong; Liu, Wenyang (Frontiers in Materials, 2021)
Composed of metallic layers and composite plies, fiber metal laminates (FMLs) combine inherent advantages of metals and composites. The phenomenon of anomalous response behavior, in which the permanent deformation is in the opposite direction to the incoming pressure wave, has been discovered in dynamic responses of monolithic plate subjected to impulsive loading. In this study, dynamic responses of FML plates of various configurations are examined and compared against the responses of a monolithic plate using finite element analysis. It is found that under the load condition in which an anomalous dynamic behavior of an aluminum plate is observed, FMLs oscillate a few cycles before resting on permanent deformation, and the laminate thickness strongly affects the final deflection, which could be in the counter-intuitive direction or near the initial position of zero deflection depending on configuration and specification of FMLs. In addition, interaction of damage accumulation with deflection responses is investigated. The findings of this study can be useful for optimal design of FMLs intended for usage under extreme loadings.